Suitability of eremospatha macrocarpa canes for the production of cement-bonded composites (2011)
"The suitability of untreated Eremospatha macrocarpa canes for cement-bonded composites (CBCs) and the effect of cold water pretreatment on the compatibility of the species with cement were investigated using the hydration test approach .Eremospatha macrocarpa particles were mixed with cement and water, and placed in insulated thermos flasks. Temperature rise was monitored for 24 hours. Suitability of the species for CBC production was assessed based on setting time (tmax), maximum hydration temperature (Tmax) and time ratio (tR). The tmax, Tmax and tR of the cement composites ranged from 7.2–8.5 hours, 55.0–57.1 °C and 1.2–1.4 respectively. Pretreatment of particles with cold water reduced the tmax, Tmax and tR of the cement composites by 15.3, 3.7 and 14.3% respectively. Cold water pretreatment significantly improved the compatibility of untreated particles of E.macrocarpa with cement. "